Investigation of the maturation effects on biomarker distributions in bituminous coals. (November 2022) - Cai, Feixuan; Wang, Ruwei; Cai, Jiawei; Huang, Qing; Huang, Zhuliang; Xu, Yuchan; Yang, Qiling
Graphical abstract: Highlights: Changes in n -alkane, terpane, and sterane indices show the combined effects of maturation and depositional environment. Pr/Ph, Pr/ n -C17, and Ph/ n -C18 ratios record the influence of depositional environment. Epimerization reactions of hopanes and steranes are affected by thermal maturity and origin. Degree of demethylation consistently depends on rank but is higher in Da Baoding coals compared to Huainan coals. Individual PACs indices show variable trends with maturity and are sensitive to organofacies. Abstract: Biomarkers in coal can evolve dramatically in terms of their concentration and distribution during coalification, limiting their use in source allocation of coal-derived pollution. Here we analyzed a broad range of aliphatics (i.e., 26 n -alkanes, 6 isoprenoids, 32 terpanes, 19 steranes) and 77 polycyclic aromatic compounds (PACs) in the Permo-Carboniferous and Late Triassic coals from the Chinese Huainan and Da Baoding coalfields, respectively. These coals, classifying as high volatile bituminous B to low volatile bituminous with vitrinite reflectance ( R r ) values ranging from 0.71 to 1.74 %, show variable organic geochemical features owing to the combined effects of thermal maturity and organofacies. Changes in the n -alkanes and isoprenoids indicate the loss of aliphatic fractions associated with maturation owing to cracking of the long-chain alkanes. The stratigraphic changes in the pristane to phytane ratios (Pr/Ph), Pr/ n -C17, and Ph/ n -C18 reflect a control exerted by the depositional environment in the Huainan coals. In addition, principal component analysis (PCA) recognizes the Pr/ n -C17, Ph/ n -C18, carbon preference index (CPI), and odd-to-even predominance 2 (OEP 2) as organofacies sensitive indices. Intercomparison of the PAC distributions suggest different maturation pathways for the coals from the Huainan and Da Baoding coalfields. The demethylation processes related to coalification preferentially occur on the polymethyl substitutes that occur to a greater degree in the Da Baoding coals than in the Huainan coals. Nine PAC indices display distinctive patterns when plotting against R r . The DMP-2 vs DBT:DBF cross-plot explicitly separates the Huainan and Da Baoding coals into three distinctive zones representing different depositional environments and sources of organic matter. Moreover, PCA explicitly discriminate the maturation sensitive indices (i.e., MNR, DNR-1, TrMN-1, TrMN, TeMN, MPR, and MPI-1) from organofacies sensitive indices (i.e., DMP-2 and DBT:DBF).